Implementasi Sistem Informasi Akademik berbasis Web pada SMAN 1 Kota Tangerang Selatan - Difa Cornelia Agustin; Ardina Nayla Latief; Jupron Jupron (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2026)
SMAN 1 Kota Tangerang Selatan requires a more integrated system to support assignment management, task submission monitoring, and academic data presentation. This study aims to implement a web-based academic information system that provides assignment management, student answer submission, task status monitoring, role-based access control, and academic dashboard visualization. The system was developed using the Waterfall method, with data collected through observation, interviews, and literature study. The application was implemented using PHP, MySQL, Bootstrap, and Chart.js, and tested using Black Box Testing. The results show that the system can help teachers manage assignments, monitor student submissions, provide grades and feedback, and present academic information through a visual dashboard.